The three great theories of suffrage - Ridenour, Ambrose Elliot (My University, 1896)
Introduction: “All governments derive their just powers from the consent of the governed.” The relation of the governed to the government was in the not far distant past, very much the same as the relation of the slave to his master. A few persons stood beneath the canopy of a throne, embodying in themselves all that might be implied in the phrase: “the divine right of kings.’ To conquer was their highest ambition. Before the sway of their scepter a nation would spring into being – a tribe be exterminated - a kingdom vanquished. They knew not right as we today interpret it. To them it might mean any wrong exercised in the interest of self-aggrandizement. Virtue with them was at its best, viewed from the present a personification of the vulgar and uncouth. What little good there was buried beneath a mountain of sorrow, suffering and pain, deceit, dishonesty and crime.
Citation: Ridenour, Ambrose Elliot. The three great theories of suffrage. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Government; Kings; Virtue; Theses; Manuscripts (documents)